BITCOIN-USD TRADING USING SVM TO DETECT THE CURRENT DAY’S TREND IN THE MARKET - Ferdiansyah Ferdiansyah; Edi Surya Negara; Yeni Widyanti (Universitas Bina Darma, 2019)
Bitcoin is a kind of Cryptocurrency and now is one of type of investment in the stock market. Stock markets are influenced by many risks of factor. And bitcoin is one kind of cryptocurrency that keep rising in recent few years, and sometimes fall without knowing influence behind it, on stock market. Because it’s fluctuations, there’s a need Automated tool to prediction of bitcoin on stock market. However, because of its volatility, there’s a need for a prediction tool for investors to help them consider investment decisions for bitcoin or another cryptocurrency trade. The predict methods will be used on this research is regime prediction to develop model to predict trend at the opening of market using SVM.